STUDYING INTERNATIONAL COMPETITIVENESS IN PHARMACEUTICAL SECTOR IN SELECTED DEVELOPED COUNTRIES - Zeinab Mousavi, Seyede; Rasekhi, Saeed; Golestani, Mina; Imani, Ali (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: Competitiveness is the ability of countries in increasing market share, profits, value added, and staying at the scene of fair and international competition for a long period of time. This is realized through market authority and establishing activities based on comparative and competitive advantages. On the other hand, the research-based pharmaceutical industry makes a major contribution to the prosperity of the world economy. It is a robust sector that has been one of the pillars of industrialized economies and is increasingly recognized as an important sector in the developing world as well. Furthermore, global sales of pharmaceutical products represent the international spread of medical technology that comes as the result of highly intensive R and D efforts in the exporting countries (International Federation of Pharmaceutical Manufacturers and Associations, 2012). The present study aimed to analyze and investigate the international competitiveness of pharmaceutical sector in selected developed countries using traditional and new indices of competitiveness. Methods: In this study, revealed comparative advantage index and also static and dynamic intra-industry trade (IIT) indices were used in the period 2000â€“2012. Results: The results indicated the growing competitiveness in most of the selected countries. Furthermore, the findings suggested that countries with higher levels of international trading of pharmaceutical goods have a higher potential of competitiveness based on IIT and comparative advantage indices. Conclusions: For increase in international competitiveness in pharmaceutical industry, selected developed countries pay attention to both comparative and competitive advantages.